Computational Techniques and their Usage to Optimize Car Design for Better Performance - Muhammad Uzair Riaz; Manzoor, Tareq; Muhammad Umair; Hasan Ali; Ammar Iqbal (Innovative Computing Review, 2021)
This paper describes the use of different computational fluid dynamics (CFD) models and other techniques that can be used to get low coefficient of drag. The upper body of a car is designed using surface modeling in CATIA. It is analyzed using K-epsilon realizable model in ANSYS Fluent. Changes in design are made based on the high coefficient of drag at high speeds. Then, K-epsilon realizable model is used for analysis. To get better accuracy, a refined mesh for the wake region is used. Afterwards, k-omega standard model is used. At the end, the upper body of the passenger car and its tyres are examined to get the final results of the coefficient of drag. The same design with the same meshing conditions is also analyzed in Star CCM+ to verify the results. INDEX TERMS: ANSYS Fluent, computational fluid dynamics (CFD), coefficient of drag, Star CCM+